(r^2) (dT/dr)+B*r*T=T^2, with initial condition dT/dr |(adsbygoogle = window.adsbygoogle || []).push({}); _{r=0}=0 where B is a constant

I've gotten it to this:

dT/dr = -BT/r + T2 / r2

by dividing everything by r2, then I substitute using λ= T/r which gives:

r * dλ/dr + lambda = -B * (λ) + λ^2

I don't know how to separate from here, any help is appreciated

**Physics Forums - The Fusion of Science and Community**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Differential Equations Help, non-linear first order with substitution

Loading...

Similar Threads - Differential Equations Help | Date |
---|---|

I Need a help in solving an equation (probably differentiation | Nov 20, 2017 |

A Please help with 2-variable partial differential equation | Nov 4, 2016 |

A Need help with a differential equation | Oct 9, 2016 |

I I need help with differential equation(3x^2-2y^2)(dy/dx)=2xy | Aug 15, 2016 |

I Help with basic problem of kinematics | Jul 2, 2016 |

**Physics Forums - The Fusion of Science and Community**